An evaluation of parental knowledge of childhood asthma in a Family Practice setting - Moosa, Sulaiman Essa Ismail (Department of Paediatrics and Child Health, 2017)
The purpose of this study was to measure and evaluate parental knowledge and misconceptions with regard to asthma and its treatment, to identify parental concerns with regard to the disease and its effects on their children, and to identify selected socio-demographic and medical correlates of the above. A cross-sectional survey was conducted among 54 families with a child with asthma. The sample comprised all the parents of a consecutive series of asthmatic patients between the ages of two to eighteen years attending a family practice in Mandalay on the Cape Flats. Data were collected by means of a structured questionnaire administered to 52 mothers and 48 fathers, reflecting a 95.2 per cent response rate. Respondents completed the questionnaire in their homes. A 55 item Asthma Knowledge Test was developed and validated to assess medical knowledge. Parents obtained an average score of 72%. Scores of over 70% were obtained in the sub-sections of aetiology, symptomatology, pathophysiology, precipitants and environmental control. Parents were less informed in the sub-sections of asthma prognosis, general medical knowledge and asthma therapy. Misconceptions and deficiencies in asthma knowledge which could lead to inadvertent non-compliance were identified. The following misconceptions were shared by a significant number of parents: inhaler therapy weakens the heart, regular administration of medication leads to addiction and medicines becoming ineffective, and folk remedies are effective in asthma therapy. Parental educational status was the only significant correlate with performance on the Asthma Knowledge Test. There was no significant difference in the performances of mothers and fathers. 47% of parents smoked but there was no significant difference in the scores of smokers and non-smokers. Parental concerns centred predominantly on their lack of confidence to manage acute asthma attacks, followed by concern as to whether their children will outgrow asthma. Dependence on asthma medication and its perceived harmful effect on the heart and lungs were other concerns. The findings suggest the need for systematic asthma education especially with regard to acute attack management and preventive medications. The aims of such education should be to increase asthma knowledge, develop skills, improve attitudes, and develop positive expectations toward the outcome and effectiveness of treatment. An effort should be undertaken to discourage parental smoking in asthmatic families. Attention should be given to dispel misconceptions during educational programmes. The increased information needs of parents with a lower education should be addressed by health professionals. Parents should receive adequate information during the early stages of the disease to minimise their insecurity in coping with the illness and prevent the development of misconceptions that undermine their confidence in medications and care givers.